The Latest Research Progress of m6A Modification and Its Writers, Erasers, Readers in Infertility: A Review - Liu, Xuda; Wang, Haiying; Liu, Bingchen; Qi, Zhipeng; Li, Jiashuo; Xu, Bin; Liu, Wei; Xu, Zhaofa; Deng, Yu (Frontiers in Cell and Developmental Biology, 2021)
Eukaryotic messenger mRNAs contain many RNA methyl chemical modifications, in which N6-methyladenosine (m6A) plays a very important role. The modification process of RNA methylation is a dynamic reversible regulatory process that is mainly catalyzed by “Writer” m6A methyltransferase, removed by “Eraser” m6A demethylase, and recognized by the m6A binding protein, thereby, linking m6A modification with other mRNA pathways. At various stages of the life cycle, m6A modification plays an extremely important role in regulating mRNA splicing, processing, translation, as well as degradation, and is associated with gametogenesis and fertility for both sexes. Normal gametogenesis is a basic guarantee of fertility. Infertility leads to trauma, affects harmony in the family and seriously affects the quality of life. We review the roles and mechanisms of RNA m6A methylation modification in infertility and provide a potential target for infertility treatment, which can be used for drug development.